Financial Development And Economic Growth : Evidence From Saarc Countries - Teoh, Christina Li Yin (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This study examines the empirical links between financial development and economic growth in SAARC countries. Unbalanced panel dataset of five SAARC countries has been taken that includes Bangladesh, India, Nepal, Pakistan and Sri Lanka over the period of 1994 to 2014. The empirical results using Fully Modified Least Squares (FMOLS) and Panel Granger Causality reveal that the banking sector development is statistically significant determinant of economic growth. On the other hand, stock market development does not statistically cause economic growth. This finding suggests that improving the functioning of banking sector is important to influence the economic growth in SAARC countries.